The effect of the floor-to-wall interaction on the rocking stiffness of segmented CLT shear-walls. (15th December 2021) - D'Arenzo, Giuseppe; Schwendner, Sascha; Seim, Werner
Highlights: An analytical model of the floor-to-wall interaction is presented. The expression of an equivalent floor-to-wall interaction spring is provided. Parametric analyses at floor and shear-wall level are conducted. Abstract: The mechanical behaviour of Cross-Laminated Timber (CLT) buildings under lateral loads is mainly governed from the connections and is strongly influenced from the internal structure of the shear-walls, which can be monolithic or segmented. In comparison with monolithic shear-walls, segmented shear-walls have a more flexible behaviour and can dissipate higher amount of energy due to the contribution of the vertical panel-to-panel connections. However, in CLT buildings other connections, such as the connections between the wall heads and the upper floor, can influence the lateral behaviour of the shear-walls. This paper presents a study on the phenomenon of the floor-to-wall interaction and on the influence of this mechanism on the rocking behaviour of segmented CLT shear-walls. An analytical elastic model that describes the floor-to-wall interaction and allows to calculate transversal displacements and internal actions along the floor is presented and validated against numerical models developed in SAP2000. The analytical model is subsequently used for the definition of an equivalent spring, which can be used for easily taking into account the more complex phenomenon of the floor-to-wall interaction. Parametric analyses, in which different geometries and connection stiffnesses were used, showed that the floor-to-wall interaction increases the rocking stiffness of segmented shear-walls and modifies the shear-wall kinematic behaviour. The increase of rocking stiffness was found to be dependent on the floor bending stiffness as well as the withdrawal stiffness of the floor-to-wall connections.